Nocturnal symptoms perceived as asthma are associated with obstructive sleep apnoea risk, but not bronchial hyper‐reactivity. Issue 12 (8th May 2019) - Senaratna, Chamara V.; Walters, E. Haydn; Hamilton, Garun; Lowe, Adrian J.; Lodge, Caroline; Burgess, John; Erbas, Bircan; Giles, Graham G.; Thomas, Paul; Abramson, Michael J.; Thompson, Bruce; Perret, Jennifer L.; et al.
ABSTRACT: Background and objective: Obstructive sleep apnoea (OSA) and asthma are associated, and nocturnal breathing difficulty that is usually identified as asthma‐like symptoms can be present in both conditions. We investigated how nocturnal asthma‐like symptoms (NAS) and bronchial hyper‐reactivity (BHR) contribute to the association between OSA risk and current asthma, which is currently unknown but a clinically important question. Methods: We used data from 794 middle‐aged participants in a population‐based cohort who provided information on OSA risk (defined by a STOP‐Bang questionnaire score of at least 3), current asthma and NAS, and underwent methacholine bronchial challenge testing. Using regression models, we examined the association between OSA risk and current asthma‐NAS subgroups and investigated any effect modification by BHR. Results: The participants were aged 50 years (49.8% male). OSA risk was associated with NAS with or without current asthma (odds ratio (OR): 2.6; 95% CI = 1.3–5.0; OR: 4.2; 95% CI = 1.1–16.1, respectively), but not with current asthma in the absence of NAS. BHR was associated with current asthma with or without NAS (OR: 2.9; 95% CI = 1.4–5.9; OR: 3.4; 95% CI = 2.0–7.0, respectively) but not with NAS in the absence of current asthma. The associations between OSA risk and current asthma were neither modified nor mediated by BHR. Conclusion: Our findings suggest that some of the nocturnal symptoms perceived as asthma may be OSA symptoms. Patients with nocturnal asthma symptoms should be considered for possible OSA. Abstract : We assessed the roles of nocturnal asthma‐like symptoms (NAS) and bronchial hyper‐reactivity (BHR) in obstructive sleep apnoea (OSA)–asthma association. OSA is associated with NAS with or without the presence of asthma, but BHR is not associated with NAS when asthma is absent. Some NAS perceived as nocturnal asthma could be symptoms of OSA. See related Editorial